2023
DOI: 10.3390/molecules28217250
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Alkali Treatment for Production of Fermentable Sugars and Phenolic Compounds from Potato Peel Waste Using Topographical Characterization and FTIR Spectroscopy

Qudsia Mushtaq,
Nicolas Joly,
Patrick Martin
et al.

Abstract: Potato peel waste (PPW) was utilized as a bio-template for the production of valuable compounds such as reducing sugars (RS), total sugar (TS) and total phenolic compounds (TPC). Two methods of alkali treatments, i.e., chemical (NaOH) and thermochemical (NaOH assisted with autoclaving) processes, were employed for the deconstruction of PPW. Response surface methodology (RSM) was used to study the effects of alkali concentration (0.6–1.0 w/v), substrate concentration (5–15 g) and time (4–8 h) on the extraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…up to 660.62 mg/gds were released after dilute sulphuric acid plus autoclaved treatment. Mushtaq et al 52 have reported high yield of total and reducing sugars upto 28.971and 7.163 mg/ml using alkali treated PPW. A previous report has described dilute sulphuric acid hydrolysis and sonication of PPW as a very promising process to release reducing sugars i.e., 57.03 g/kg 53 .…”
Section: Resultsmentioning
confidence: 99%
“…up to 660.62 mg/gds were released after dilute sulphuric acid plus autoclaved treatment. Mushtaq et al 52 have reported high yield of total and reducing sugars upto 28.971and 7.163 mg/ml using alkali treated PPW. A previous report has described dilute sulphuric acid hydrolysis and sonication of PPW as a very promising process to release reducing sugars i.e., 57.03 g/kg 53 .…”
Section: Resultsmentioning
confidence: 99%
“…The key areas of industry where amylases and cellulases are increasingly being applied are in textile, healthcare, pulp, paper, detergent, food, beverages, pharmaceutical, biofuel, and pretreatment methods [ 17 , 18 , 19 , 20 , 21 , 22 ]. Various research reports have investigated the potential of PPW enzyme production and various other value-added products [ 7 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%